2023
DOI: 10.3390/life13010168
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Provides Novel Insights into the Heat Stress-Induced Response in Codonopsis tangshen

Abstract: Codonopsis tangshen Oliv (C. tangshen) is a valuable traditional Chinese medicinal herb with tremendous health benefits. However, the growth and development of C. tangshen are seriously affected by high temperatures. Therefore, understanding the molecular responses of C. tangshen to high-temperature stress is imperative to improve its thermotolerance. Here, RNA-Seq analysis was performed to investigate the genome-wide transcriptional changes in C. tangshen in response to short-term heat stress. Heat stress sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Similarly, our results demonstrated that chlorophyll (Chl a, Chl b) content declined after continuous cropping. One study showed the level of antioxidant enzymes SOD and the stress marker malonaldehyde (MDA) in the cells reflected the degree of oxidative damage [ 16 , 19 ]. In the present study, LZ significantly reduced the SOD activity and enhanced the MDA content, suggesting that the reduced SOD activity causing oxidative damage was indicated by increased malonaldehyde (MDA) contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, our results demonstrated that chlorophyll (Chl a, Chl b) content declined after continuous cropping. One study showed the level of antioxidant enzymes SOD and the stress marker malonaldehyde (MDA) in the cells reflected the degree of oxidative damage [ 16 , 19 ]. In the present study, LZ significantly reduced the SOD activity and enhanced the MDA content, suggesting that the reduced SOD activity causing oxidative damage was indicated by increased malonaldehyde (MDA) contents.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used in this study are listed in Table S1 . The 2 −ΔΔCT method was used to determine the relative expression of genes [ 16 ]. One-way ANOVA was applied to analyze the statistical differences between different groups.…”
Section: Methodsmentioning
confidence: 99%